Survival Outcomes of Patients Treated with Hypofractionated Stereotactic Body Radiation Therapy for Parotid Gland Tumors: a Retrospective Analysis - Karam, Sana D.; Snider, James W.; Wang, Hongkun; Wooster, Margaux; Lominska, Christopher; Deeken, John F.; Newkirk, Kenneth; Davidson, Bruce; Harter, K.William (Frontiers in Oncology, 2012)
Background: to review a single-institution experience with the management of parotid malignancies treated by fractionated stereotactic body radiosurgery (SBRT). Findings: Between 2003 and 2011, 13 patients diagnosed with parotid malignancies were treated with adjuvant or definitive SBRT to a median dose of 33 Gy (range 25–40 Gy). There were 11 male and two female patients with a median age of 80. Ten patients declined conventional radiation treatment and three patients had received prior unrelated radiation therapy to neighboring structures with unavailable radiation records. Six patients were treated with definitive intent while seven patients were treated adjuvantly for adverse surgical or pathologic features. Five patients had clinical or pathologic evidence of lymph node disease. Conclusion: at a median follow-up of 14 months only one patient failed locally, and four failed distantly. The actuarial 2-year overall survival, progression-free survival, and local-regional control rates were 46, 84, and 47%, respectively. Statistical analysis revealed surgery as a positive predictor of overall survival while presence of gross disease was a negatively correlated factor (p < 0.05).